2012
DOI: 10.1186/1478-811x-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic subcellular localization of the mono-ADP-ribosyltransferase ARTD10 and interaction with the ubiquitin receptor p62

Abstract: BackgroundADP-ribosylation is a posttranslational modification catalyzed in cells by ADP-ribosyltransferases (ARTD or PARP enzymes). The ARTD family consists of 17 members. Some ARTDs modify their substrates by adding ADP-ribose in an iterative process, thereby synthesizing ADP-ribose polymers, the best-studied example being ARTD1/PARP1. Other ARTDs appear to mono-ADP-ribosylate their substrates and are unable to form polymers. The founding member of this latter subclass is ARTD10/PARP10, which we identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…Flag-PARP12L, Flag-PARP7, and Flag-PARP10 proteins were detected in the cells in small granules. In support of the previously published data, Flag-PARP10 was found to also form larger, spherical complexes (42). Flag-PARP12-C accumulated both in small granules and in larger complexes, and this likely explains the detection of high-molecular-weight complexes in the sucrose gradients even after RNase A or EDTA treatments.…”
Section: Parp7 Papr10supporting
confidence: 76%
“…Flag-PARP12L, Flag-PARP7, and Flag-PARP10 proteins were detected in the cells in small granules. In support of the previously published data, Flag-PARP10 was found to also form larger, spherical complexes (42). Flag-PARP12-C accumulated both in small granules and in larger complexes, and this likely explains the detection of high-molecular-weight complexes in the sucrose gradients even after RNase A or EDTA treatments.…”
Section: Parp7 Papr10supporting
confidence: 76%
“…ARTD10 is predominantly cytosolic under basal conditions and forms discrete and dynamic 'bodies' in the cytoplasm [25]. In the present study, we first confirmed the cellular localisation of ARTD10, and then we extended our search to its target proteins.…”
Section: Artd10 Localises In Membrane-free Cell Bodiessupporting
confidence: 69%
“…ARTD10 shuttles between cytoplasm and nucleus (Kleine et al, 2012) and the results provide additional evidence for the role of ARTD10 in S phase DNA damage repair. OUL35 will aid further studies to assess the roles of ARTD10 in different processes.…”
Section: Discussionmentioning
confidence: 63%